In vitro and in vivo antiherpetic activity of three new synthetic brassinosteroid analogues - Michelini, Flavia Mariana (2004)
Brassinosteroids are a novel group of steroids that appear to be ubiquitous in plants and are essential for normal plant growth and development. It has been previously reported that brassinosteroid analogues exert an antiviral activity against herpes simplex virus type 1 (HSV-1) and arenaviruses. In the present study, we report the chemical synthesis of compounds (22S,23S)-3β-bromo-5α,22,23-trihydroxystigmastan-6-one (2), (22S,23S)-5α-fluoro-3β-22,23-trihydroxystigmastan-6-one (3), (22S,23S)-3β,5α,22,23-tetrahydroxy-stigmastan-6-one (4) as well as their antiherpetic activity both in a human conjunctive cell line (IOBA-NHC) and in the murine herpetic stromal keratitis (HSK) experimental model. All compounds prevented HSV-1 multiplication in NHC cells in a dose dependent manner when added after infection with no cytotoxicity. Administration of compounds 2, 3, and 4 to the eyes of mice at 1, 2, and 3 days post-infection delayed and reduced the incidence of HSK, consisting mainly of inflammation, vascularization, and necrosis, compared to untreated, infected mice. However, viral titers of eye washes showed no differences among samples from treated and untreated mice. Since the decrease in the percentage of mice with ocular lesions occurred 5 days after treatment had ended, we suggest that brassinosteroids 2, 3, and 4 did not exert a direct antiviral effect in vivo, but rather may play a role in immune-mediated stromal inflammation, which would explain the improvement of the clinical signs of HSK observed.